PENGARUH APLIKASI PUPUK CAIR LIMBAH IKAN DAN BUBUK AKTIF AHL TERHADAP PERBAIKAN KANDUNGAN N DAN P TANAH ALFISOL DAN HASIL TOMAT - IN Prijo Soetedjo; Y I. Benggu; Max Kappa; A B. Tupen (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Nusa Cendana, 2023)
Alfisol is one of soil type which is a high accumulation of clay on above horizons. This conditions result in a high soil compaction which cause difficulty penetration of plant root. Moreover, this type of soil is low organic matter resulted in low nutrients content such as Nitrogen, Phosphorus and Potassium. A research had been conducted at village of East Penfui, District of Kupang since May to August 2022. Main aim of the research was to determine effect various concentration of fish waste liquid fertilizer and active powder of AHL in improving levels contain of Phosphorus, and Potassium and yield of tomato. The research was designed Completed Random Designed with three replications. Treatments of the research were control (LO), 15 ml liquid fertilizer of fish waste (L1), 25 ml liquid fertilizer of fish waste (L2), 35 ml liquid fertilizer of fish waste (L3), 45 ml liquid fertilizer of fish waste (L4), 15 ml liquid fertilizer of fish waste (L5) + 0.2 g active powder of AHL, 25 ml liquid fertilizer of fish waste (L5) + 0.2 g active powder of AHL (L6), 35 ml liquid fertilizer of fish waste (L5) + 0.2 g active powder of AHL (L7), and 45 ml liquid fertilizer of fish waste (L5) + 0.2 g active powder of AHL (L8). Parameters measurements were available of Phosphorus, total Nitrogen and Yield of Tomato. All data were analyzed by using Analysis of Variant followed by Duncan Multiple Range Test at 5% level. Result of the research showed that application of 45 ml liquid fertilizer of fish waste (L5) + 0.2 g active powder of AHL (L8) resulted significantly highest contents of available of Phosphorus (33.41 ppm), total Nitroegn (1.23%). Meanwhile, application of 25 ml liquid fertilizer of fish waste (L5) + 0.2 g active powder of AHL (L6) resulted a highest of of tomato by 526.22 g per plant which is not significantly different to application of 45 ml liquid fertilizer of fish waste (L5) + 0.2 g active powder of AHL (L8)